Carry-over effect of immunotherapy in patients with advanced hepatocellular carcinoma - Chien-Huai Chuang; Ching-Tso Chen; Chih-Hung Hsu; Yu-Yun Shao (Cancer Immunology, Immunotherapy)
Abstract Background Combination immunotherapy is the current standard for treating advanced hepatocellular carcinoma (HCC). The response elicited by upfront immune checkpoint inhibitors (ICIs) might influence the efficacy of salvage therapy, a phenomenon known as the carry-over effect. This effect is thought to stem from immune memory and sustained immune activation, providing extended protection against tumor progression and resulting in a durable response even after discontinuation of ICI. This study aimed to investigate the carry-over effect of first-line ICI therapy in patients with advanced HCC. Methods Patients who received first-line ICI therapy for advanced HCC from December 2017 to December 2021 were included if they exhibited disease progression and received second-line systemic therapy. We analyzed the associations between clinical benefit (classified as complete, partial response and stable disease) of first-line ICI therapy, post-progression survival (PPS) and second-line progression-free survival (PFS). We used a historical cohort of patients receiving first-line multikinase inhibitor (MKI) for comparison. Results A total of 137 patients were analyzed. We included 60 patients who received first-line ICI therapy, of which clinical benefit was detected in 46 (76.7%). Compared with patients without clinical benefit of first-line ICI therapy, patients with clinical benefit exhibited significantly longer PPS (median: 14.6 vs. 4.9 months, P = 0.024) and second-line PFS (median: 3.6 vs. 1.6 months, P = 0.027). In multivariate analysis, clinical benefit of first-line ICI therapy remained an independent predictor of PPS [hazard ratio (HR): 0.295, P = 0.005] and second-line PFS (HR: 0.484, P = 0.047). Conversely, clinical benefit was not associated with PPS among patients receiving first-line MKI therapy in both univariate and multivariate analysis in historical MKI cohort. Conclusions Clinical benefit of first-line ICI therapy was associated with PPS and second-line PFS in patients with advanced HCC, suggestive of the carry-over effect of ICI.